Micromotion compensation using dark and bright ion species - Barnea, Orr; Einav, Dror; Drotleff, Jonas; Hochner, Idan; Meir, Ziv (Frontiers in Quantum Science and Technology, 2025)
Stray electric fields induce excess micromotion in ion traps, limiting experimental performance. We present a new micromotion-compensation technique that utilizes a dark ion in a multi-species bright-dark-bright linear ion crystal. Stray electric fields in the radial plane of the trap deform the crystal axially due to the different masses of dark and bright ions. We exploit the mode softening near the transition to the zig-zag configuration to enhance the crystal deformation and, as a result, increase the method’s sensitivity dramatically. We corroborate our results with a modified ion-displacement compensation method using a single bright ion. Our modification allows us to compensate stray fields on the 2D radial plane from a 1D measurement of the ion position on the camera by controlling the asymmetry of the two radial modes of the trap. Both methods require only a fixed imaging camera and continuous ion-fluorescence detection. As such, they can be readily implemented in most ion-trapping experiments without additional hardware modifications.